2005
DOI: 10.1007/s11176-005-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photophysical Properties of Mixed-Ligand Cyclometallated Complexes of Ir(III) with a Dendritic Bipyridine Ligand

Abstract: Complexes [Ir(C^N) 2 (G1-bpy)]PF 6 , where C^N is a cyclometallating ligand derived from 2-(2`-thienyl)pyridine and 2-phenylpyridine, and G1-bpy is a dendritic bipyridine ligand of the first generation, 4,4`-bis[3",5"-bis(benzyloxy)phenylethyl]-2,2`-bipyridine, were prepared and characterized by 1 H NMR, electronic absorption, and emission spectroscopy. The polyether dendritic substituents exert a [soft] effect on the spectral and luminescence properties of the complexes, manifested as slight destabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The current is higher in the OLED using the neat G1 level system than those using the dendrimer consisting of the Ir(ppy) 3 core and phenylene-based dendrons 204 indicating that the dendrimer's hole drift mobility was enhanced by the hole-transporting dendrons. Balashev and co-workers 205 synthesized Ir-based complexes [Ir(C^N) 2 (G1-bpy)(PF 6 )], where C^N is a cyclometallating ligand derived from 2-(2 0 -thienyl)pyridine and 2-phenylpyridine, and G1-bpy is 4,4 0 -bis[3 00 ,5 00 -bis(benzyloxy)phenylethyl]-2,2 0 -bipyridine. Their studies demonstrated that the luminescence behavior of the mixed-ligand Ir(III) complexes with a dendritic bipyridine ligand strongly depended on the cyclometalating ligand, temperature, and matrix (effect of the hardness and polarity).…”
Section: Luminescencementioning
confidence: 99%
“…The current is higher in the OLED using the neat G1 level system than those using the dendrimer consisting of the Ir(ppy) 3 core and phenylene-based dendrons 204 indicating that the dendrimer's hole drift mobility was enhanced by the hole-transporting dendrons. Balashev and co-workers 205 synthesized Ir-based complexes [Ir(C^N) 2 (G1-bpy)(PF 6 )], where C^N is a cyclometallating ligand derived from 2-(2 0 -thienyl)pyridine and 2-phenylpyridine, and G1-bpy is 4,4 0 -bis[3 00 ,5 00 -bis(benzyloxy)phenylethyl]-2,2 0 -bipyridine. Their studies demonstrated that the luminescence behavior of the mixed-ligand Ir(III) complexes with a dendritic bipyridine ligand strongly depended on the cyclometalating ligand, temperature, and matrix (effect of the hardness and polarity).…”
Section: Luminescencementioning
confidence: 99%